Asuhan Keperawatan Medikal Bedah Pada Pasien Dengan Dangue Hemoragic Fever (DHF) Di Ruang Rawat Inap RSUD Prof M,Yamin Pariaman - Nadila Nahdatul Huda; Hilma Yessi; Debby Silvia Dewi; Linda Marni (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus and transmitted through the bites of Aedes aegypti and Aedes albopictus mosquitoes. DHF remains a major public health problem in Indonesia due to its high incidence rate. This scientific paper aimed to describe the implementation of nursing care for a patient with DHF. The method used was a case study applying the nursing process, including assessment, nursing diagnosis, planning, implementation, and evaluation. The subject of the study was one patient (Ms. N) who was hospitalized for five days in the Internal Medicine Ward of Prof. M. Yamin Hospital, Pariaman. The results revealed four nursing diagnoses: hypovolemia, hyperthermia, risk for bleeding, and risk for nutritional deficit. After comprehensive nursing interventions were provided, the patient's condition improved as evidenced by normal body temperature, increased platelet count, adequate fluid balance, and improved nutritional intake. The study concludes that systematic, comprehensive, and continuous nursing care is effective in improving patient outcomes and accelerating recovery in patients with DHF.